The Sybmols of National History in Lithuanian National Imagination: the Images of National Heroes - Šutinienė, Irena (Sociologija. Mintis ir veiksmas, 2009)
The article concerns the issues of the symbolic re-imagination of the nation – how the symbols of the national narrative of Lithuanian past are re-constructed in the popular imagination of the society and its groups. The popular reception and interpretations of the images of the heroes of the narrative of national history as well as trends of their change are analysed on the basis of the data of longitudinal quantitative research conducted in 1991, 1992 and 2007. The questions of the authority of the traditional heroes in the conditions of the erosion of metanarratives, the trends of changes of popular interpretations of the heroes, the tendencies of continuity and discontinuity of those interpetations as well as the divisive and unifying potential of the popular images of the heroes are examined in the analysis. Though the symbolic power of the images of national heroes is less than in 1991–1992, they still evoke sentiments and exert influence. The tendencies of erosion of traditional myths as well as continuity of the basic structures of the “pantheon” of Lithuanian heroes as well as the tendencies of hybridization of popular narratives of Lithuanians and Polish minority are observed. The contradictory interpretations of some images by Poles and Lithuanians seem to function as the relicts of memory of interwar conflict mostly located in the collective memory of the older generations living in the regions that former belonged to Poland.